2017
DOI: 10.17221/51/2016-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding of four blast resistance QTLs into Thai rice cultivar RD6 through marker-assisted selection

Abstract: Suwannual T., Chankaew S., Monkham T., Saksirirat W., Sanitchon J. (2017): Pyramiding of four blast resistance QTLs into Thai rice cultivar RD6 through marker-assisted selection. Czech J. Genet. Plant Breed., 53: 1-8.Thai rice cultivar RD6 is well known for its cooking and eating qualities. However it is susceptible to blast disease, a major rice disease caused by the fungus Magnaporthe oryzae. This study focused on the pyramiding of four QTLs for blast resistance located on chromosomes 1, 2, 11 and 12, from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Hence, we expect that it could be easily promoted among farmers who have shown a preference for the original RD6, thus negating the need to further backcross with RD6 again. Similar to the findings of Suwannual et al [14] and Pinta et al [15], we observed that the use of a pseudo-backcrossing design and MAB for two generations without genetic background selection was sufficient to recover the majority of the desired characteristics of the original RD6 within the BC 2 F 5 generation.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Hence, we expect that it could be easily promoted among farmers who have shown a preference for the original RD6, thus negating the need to further backcross with RD6 again. Similar to the findings of Suwannual et al [14] and Pinta et al [15], we observed that the use of a pseudo-backcrossing design and MAB for two generations without genetic background selection was sufficient to recover the majority of the desired characteristics of the original RD6 within the BC 2 F 5 generation.…”
Section: Discussionsupporting
confidence: 89%
“…They therefore achieved consumer preference due to their excellent swelling capacity, sweetness, aroma, grain shape and size, and stickiness, i.e., like that of the original RD6 (Table 8). Our research clearly proved that a cross between glutinous and nonglutinous varieties [14,15] was possible through the conversion of glutinous RD6 NIL, resulting in effective resistance to blast and BB, as well as possessing excellent qualities.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations